Improving Phosphate Flotation With New Chemistry, Smart Flowsheet And Novel Equipment - P. Zhang (Society for Mining, Metallurgy & Exploration, 2004)
The Crago “Double Float” process is widely used in upgrading phosphate ore. This process is inefficient, as it floats about 30-40% of the sands in the flotation feed twice and requires a deoiling step. This paper summarizes several research projects on improving phosphate flotation. The University of Utah investigated a new flotation chemistry for efficient flotation of phosphate in a single step. The Florida Institute of Phosphate Research developed several single-collector, all-anionic flotation flowsheets using various sizing schemes. In addition, Eriez invented the HydroFloat separator, which demonstrated great potential for processing coarse flotation feed in one step.